Prosody growth and reading comprehension: a longitudinal study from 2nd through the end of 3rd grade - Lopes, João A. (2015)
Prosody is an important but not fully understood component of reading. In this longitudinal study with a sample of 98 Portuguese elementary school children, a multilevel growth model with four repeated measures over time showed steady progress in participants’ reading prosody from the middle of 2nd to the end of 3rd grade. However, children’s growth in this area varied across time points. Results also showed that individual differences in prosody’s scores at baseline affect the performance of most but not of all students. Simple linear regressions showed that the prosody dimension “phrasing/expression” significantly predicted reading comprehension at all time points. Partial correlation analysis showed that when reading rate was accounted for, the unique contribution of prosody to reading comprehension was marginal, except at the third measurement